The renegotiation of concession contracts in Peru. A theoretical and empirical approach to their causes and consequences - Quiñones Alayza, María Teresa (2019)
The Peruvian Government decided to use Public-Private Partnerships as a tool in its infrastructure policy. However, the constant amendments to the legal framework, the delays in the execution of projects and the frequent addend to concession contracts (specifically, those which are co-financed) have created distrust in society and affected the credibility of this model.This article analyses the main causes foref renegotiation of concession contracts awarded by ProInversión and the derived costs of excessive renegotiation. Our data shows that the benefits that the Peruvian Government obtains by acting opportunistically: i.e., by awarding projects that lack sufficient studies or an adequate risk assignment, are countered by the impact on the legitimacy of Public-Private Partnerships and by the delays in the completion of projects destined to attend public needs. However, our research shows that the Government is prone to prioritize the benefits it receives in the short term disregarding the long term costs that a premature awarding of projects entails.